Comparison of NOD-like and Toll-like receptors gene expression levels in blood monocytes of colon cancer patients: NOD-like and Toll-like receptors’ genes in colon cancer patients - Meng, Feilong; Yang, Juan; Hua, Shuai; Zhang, Ying; Fu, Xinnian; Ma, Chi; Wang, Xinxin; Fu, Zhipeng; Zheng, Sheng (Cellular and Molecular Biology, 2023)
Colon cancer is one of the most common cancers affecting many people worldwide. This disease can be treated if diagnosed in the early stages. Therefore, with the hypothesis that the level of expression of inflammatory genes in peripheral blood monocytes of patients with colon cancer is different from that of healthy people, this research was done to find out the role of inflammation in the development of colon cancer by relying on its immunopathological profile to help diagnose it in the early stages. In this case-control study, the expression levels of TLR4, TLR2, NLRP3, and NOS2 genes in 15 patients with confirmed stage II colon cancer were determined by the TNM method. Also, 15 healthy people referred for this cancer screening were selected as the control group. First, RNA was extracted from the blood monocytes of two groups, and after making cDNA, the comparison was created using the qPCR method. In this study, the β-actin gene was used as a reference gene. The expression levels of TLR2 and TLR4 at the mRNA level were significantly lower in colon cancer patients compared to the healthy control group (P<0.05). The expression level of NLRP3 in the group of colon cancer patients showed a relative increase. Still, it was not significant, while the expression level of the NOS2 gene in the group of colon cancer patients increased significantly compared to the healthy control group (P<0.05). Considering the significant changes in TLR4, TLR2, and NOS2 gene expression in monocytes of patients with grade II colon cancer and the role of inflammatory reactions in the development of this cancer, these findings can be used to diagnose and determine the prognosis. However, this requires further studies.